Children and youth with type 1 diabetes developing concomitant autoimmune disease do not exhibit worsening metabolic control or growth impairment. (July 2014) - Soni, Astha; Shaw, Emily Jayne; Natarajan, Anuja; Ng, Sze May
Abstract This study aimed to evaluate the effect of type 1 diabetes mellitus (T1DM) and concurrent autoimmune condition (AI) on glycaemic control and growth in children. Twenty‐eight children with T1DM and associated autoimmune condition were matched by sex and age at onset with two controls each. HbA1c, height standard deviation scores (SDS), weight SDS and BMI SDS were measured between six months and five years after developing T1DM. We included 28 children with T1DM and AI (10 males) and 56 (20 males) age and sex matched controls with T1DM. Out of the 28 patients with AI conditions, 21 (75%) had coeliac disease (CD), eight (28%) had autoimmune hypothyroidism (AH) and one (4%) patient had both CD and AH. Development of an AI condition occurred at 2.3 ± 3.1 years after diagnosis of T1DM. There was no significant difference in growth parameters between children in the AI group compared with controls from diagnosis to five years after diagnosis of T1DM. Children in the AI group had a significantly better HbA1c control six months after diagnosis, but no significance was noted at one, two, three and five years. Multiple logistic regression of factors showed no independent risk factors that affected the development of an AI. Suboptimal therapeutic control of an autoimmune condition such as coeliac disease and T1DM is known to lead to impairment in growth and substantial morbidity. Our study shows children with T1DM developing a concurrent autoimmune disease were not at risk of worsening metabolic control or growth impairment in the long term. Copyright © 2014 John Wiley & Sons, Ltd.